Genome‐wide identification of mitogen‐activated protein kinase (MAPK) gene family in yellow catfish (Pelteobagrus fulviadraco) and their expression profiling under the challenge of Aeromonas hydrophila. Issue 3 (17th July 2022) - Li, Ronghui; Shu, Mingyu; Liu, Xuanxuan; Nei, Zhiwei; Ye, Ben; Wang, Heyu; Gong, Yifu
Abstract: As serine/threonine protein kinases, mitogen‐activated protein kinases ( MAPK ) take part in cellular metabolism. This work found 14 MAPK genes in the yellow catfish ( Pelteobagrus fulviadraco ) genome and evaluated their taxonomy, conserved domains and evolutionary linkages for a better understanding of the MAPK gene family's evolutionary relationship and antibacterial immune response. The findings revealed that several MAPK genes are activated in response to immunological and inflammatory responses. Collinearity research revealed that in yellow catfish and zebrafish, there are six pairs of highly similar MAPK genes, indicating that these genes have been more conserved throughout evolution. The MAPK gene quantification findings revealed that JNK1a, JNK1b, p38delta and p38alpha b expression levels were considerably upregulated, indicating that they act in fish innate immunity. The findings implied that MAPK genes may involve in defence against detrimental microbe in yellow catfish, which will help researchers better understand how MAPK genes work in the innate immune system.